2018
DOI: 10.21059/buletinpeternak.v42i1.24772
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Jack Bean (Canavalia ensiformis) Meal as a Substitute for Soybean Meal in Diet for Broiler Reared for 35 Days

Abstract: This study was aimed to evaluate the utilization of jack bean meal as a substitution of soybean meal in the diets and the effect on broiler performance. A total number of two hundred Lohmann MB 202 Platinum broiler chickens were kept in five weeks rearing period, consisted of three weeks of starter phase (0-3 weeks) and two weeks of finisher phase (3-5 weeks). This study used a completely randomized design with four treatments and five replicates. The dietary treatments were: JB 0-0 (control ration: basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this study, the crude protein content of jack beans reached 27.64% (Table 1). [4], stated that the use of jack beans replaced 50% of protein from soybean meal in the broiler diet . Therefore, it did not have a negative impact on the performance, PER, and internal organs of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the crude protein content of jack beans reached 27.64% (Table 1). [4], stated that the use of jack beans replaced 50% of protein from soybean meal in the broiler diet . Therefore, it did not have a negative impact on the performance, PER, and internal organs of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The jack beans do not affect broiler performance. Therefore, they can be used as feed ingredients for local protein sources [3,4] stated that the jack beans with oaked with water at room temperature for 24 hours then boiled for 20 minute could be used as a substitute for 50% soybean meal protein without affecting the performance, carcass, and internal organs of 35-day-old broiler chickens. [5] stated that using jack beans did not affect the size of broiler chickens' digestive and accessory organs.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mahardhika et al [3] also reported that the increased pancreatic weight could be mitigated by using protease enzymes. Sudarman et al [4] reported successful substitution of soybean meal with jackbean meal at levels of 50% in both the starter and finisher phases without observing any adverse effects on the performance, carcass, and organs of 35-day-old broiler chickens. These contrasting findings emphasize the importance of conducting more research to reach a definitive conclusion on the optimal utilization of jackbean meal in poultry feed formulations.…”
Section: Introductionmentioning
confidence: 99%